Advanced health technology managing risk while tackling barriers to rapid acceleration - Douville, Sherri (Productivity Press, 2023)
"Everything worth winning in life boils down to teamwork and leadership. In my positions as a businessman, athlete, community leader, and University trustee, there are tremendous parallels between all of these endeavors that mirror an extreme team sport such as medical technology. Understanding the game, defining the game, playing your position at your highest performance, and helping others play their best game. Advanced Health Technology represents an incredible opportunity to level up the game of healthcare and highlights the multiple disciplines - or positions to be mastered - while laying out winning plays to make that next level happen." Ronnie Lott, Managing Member, Lott Investments; Member, Pro Football Hall of Fame, and Trustee, Santa Clara University Healthcare stakeholders are paralyzed from making progress as risks explode in volume and complexity. This book will help readers understand how to manage and transcend risks to drive the quadruple aim of improved patient experiences, better patient and business outcomes, improved clinician experience, and lower healthcare costs, and also help readers learn from working successful examples across projects, programs, and careers to get ahead of these multidisciplinary healthcare risks.